Technology, Physical Culture, Physical Activity, and Sport: Analysis of High School Students' Perceptions (Impetus, 2026)
This qualitative study aims to understand the knowledge and perceptions that high school students develop regarding physical culture, physical education, and sport, as well as their views on alternative practices or access through other means, including technology. This type of research allows for the recovery of experiences from individuals and social groups to generate understanding of needs and create solutions. The study population consisted of high school students from a Mexican public university. A representative sample of 112 students was selected (based on student delegation, municipality, gender, age, and shift) from different shifts and grade levels, resulting in 56 females and 56 males between 15 and 18 years of age. The primary data collection method was discussion groups, with five constructs and their triggers. Subsequently, transcription and discourse analysis were performed to create representations of students‘ perceptions about physical-sports practice with and without the use of digital and virtual technology. Thematic analysis guided this process. Among the main findings, students showed an ambiguous but positive conceptualization of the concepts of physical culture, physical activity, and sport. Regarding the integration of technology into physical activity, both genders expressed a clear interest, though with differing perspectives and emphasis. Female students tended to see technology as a direct motivator for engaging in physical activity, while male students perceived it more as a support tool. This research is necessary to identify problems and act with specific strategies, in this case, options to facilitate access to sports practices.
Keywords: Student perception; Physical culture; Physical education; Sport; Digital technology; Virtual tools; High school youth